Relationship Between Physical Disability, Disease Activity and Osteoporosis in Patients With Rheumatoid Arthritis - Mihailov Claudia ILEANA; Mitroi Adrian NELUTU (Archives of Rheumatology, 2014)
Objectives: This study aims to assess the relationship between the physical disability, degree of disease activity, and bone mineral density in menopause patients diagnosed with rheumatoid arthritis (RA). Patients and methods: The study included 130 females (mean age 62.77Å}7.51 years; range 57 to 69 years) who reached menopause, and were diagnosed with RA. Bone mineral density was measured at the lumbar spine level and femur (femur head, entire femur) through osteodensitometry with dual X-ray absorptiometry. Age, weight, height, body mass index, environment (urban, rural), age of the menarche and the onset of menopause, duration of menopause, smoker/non-smoker status, RA stage, RA onset age, duration of RA, extra-articular manifestations, the presence of rheumatoid factor, erythrocyte sedimentation rate, C reactive protein, disease activity score 28, and physical disability quantified by modified health assessment questionnaire were used for evaluating the RA activity. Results: The mean body mass index was 27.74Å}4.37 kg/m2, the mean duration of menopause was 16.42Å}8.15 years. About 44.62% of the patients had osteoporosis. Osteoporosis frequency increased with RA stage: 23.81% in stage II, 55.0% in stage III, and 77.78% in stage IV. About 58% of the patients received prednisone treatment. Independent risk factors for osteoporosis were: age, environment, body mass index, duration of menopause, rheumatoid factor presence and extra-articular manifestations, duration of RA, modified health assessment questionnaire, erythrocyte sedimentation rate and C reactive protein. Conclusion: Physical disability and disease activity contribute to the occurrence of osteoporosis in patients diagnosed with RA.